Gender Differences in Physical Activity Levels Among Overweight and Obese Medical Students During and After the COVID-19 Pandemic: A Single-Center Cross-Sectional Study - Bartosz Bogusz Adamczak; Aureliusz Andrzej Kosendiak; Zofia Kuźnik; Szymon Makles; Weronika Hariasz (Obesities)
The COVID-19 pandemic profoundly affected the physical activity (PA) patterns of various social groups, including medical students. This study aims to compare the levels of PA, expressed in metabolic equivalent of task minutes per week (MET-m/w), among overweight and obese medical students, during and after the pandemic. The pandemic period was defined as spanning from 2020 to 16 May 2022, while the post-pandemic period covered the second half of 2022 through the end of 2023. PA levels were assessed using the International Physical Activity Questionnaire (IPAQ), and Body Mass Index (BMI) was calculated based on self-reported weight and height. Only individuals with a BMI ≥ 25 kg/m2 were included. In total, 233 medical students from Wroclaw Medical University were assessed during the pandemic, and 217 post-pandemic. PA was categorized into walking, moderate, and vigorous with total MET-m/w calculated. During the pandemic, no significant gender differences were observed in walking, moderate, vigorous, or total PA. Post-pandemic, males demonstrated significantly higher levels of vigorous PA (p < 0.001) and total MET-m/w (p < 0.0001) compared to females. These findings underscore the necessity for targeted interventions promoting PA among overweight and obese medical students, especially among females.